Discovery of (3S, 4S)-3-methyl-3-(4-fluorophenyl)-4-(4-(1, 1, 1, 3, 3, 3-hexafluoro-2-hydroxyprop-2-yl)phenyl)pyrrolidines as novel RORγt inverse agonists. Issue 17 (1st September 2020) - Jiang, Bin; Duan, James J.-W.; Stachura, Sylwia; Karmakar, Ananta; Hemagiri, Hemalatha; Raut, Dhanya Kumar; Gupta, Arun Kumar; Weigelt, Carolyn A.; Khan, Javed; Sack, John S.; Wu, Dauh-Rurng; Yarde, Melissa; et al.
Graphical abstract: Abstract: A novel series of cis -3, 4-diphenylpyrrolidines were designed as RORγt inverse agonists based on the binding conformation of previously reported bicyclic sulfonamide 1 . Preliminary synthesis and structure–activity relationship (SAR) study established (3 S, 4 S )-3-methyl-3-(4-fluorophenyl)-4-(4-(1, 1, 1, 3, 3, 3-hexafluoro-2-hydroxyprop-2-yl)phenyl)pyrrolidine as the most effective scaffold. Subsequent SAR optimization led to identification of a piperidinyl carboxamide 31, which was potent against RORγt (EC50 of 61 nM in an inverse agonist assay), selective relative to RORα, RORβ, LXRα and LXRβ, and stable in human and mouse liver microsomes. Furthermore, compound 31 exhibited considerably lower PXR Ymax (46%) and emerged as a promising lead. The binding mode of the diphenylpyrrolidine series was established with an X-ray co-crystal structure of 10A /RORγt.